2006
DOI: 10.1191/0960327106ht637oa
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the protective effect between deferoxamine and deferiprone on chronic iron overload induced cardiotoxicity in rats

Abstract: Patients with iron overload frequently suffer from hemochromatosis of major organs, such as the heart and liver. Heart affection is the most common cause of death in patients with iron overload. Although the beneficial effects of deferoxamine (DFO) on iron-associated mortality are well documented, the role of deferiprone in the management of transfusional iron overload is controversial. The aim of this study was to compare the protective effect of iron chelators (DFO and deferiprone) individually and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…The significant increase in cardiac MRI T2* among our DFP-treated patients post-vitamin C supplementation could be expected because DFP therapy, either as monotherapy or in combination with DFO, has been shown to improve right and left ventricular ejection fraction which may further contribute to improved cardiac function (53)(54)(55). Emara et al (13) reported that treatment with DFP alone showed mild swelling of cardiac muscle fibers, while, on addition of vita-min C, the cardiac tissue appeared ultrastructurally more or less normal.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The significant increase in cardiac MRI T2* among our DFP-treated patients post-vitamin C supplementation could be expected because DFP therapy, either as monotherapy or in combination with DFO, has been shown to improve right and left ventricular ejection fraction which may further contribute to improved cardiac function (53)(54)(55). Emara et al (13) reported that treatment with DFP alone showed mild swelling of cardiac muscle fibers, while, on addition of vita-min C, the cardiac tissue appeared ultrastructurally more or less normal.…”
Section: Discussionmentioning
confidence: 86%
“…Emara et al . reported that treatment with DFP alone showed mild swelling of cardiac muscle fibers, while, on addition of vitamin C, the cardiac tissue appeared ultrastructurally more or less normal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The imbalance between ROS production and antioxidant defenses is called oxidative stress (Emara et al 2006;Aldubayan et al 2019). A range of non-enzymatic and enzymatic antioxidant systems that work to maintain a healthy ROS balance has been described by Lim (2014) and are investigated for their bene cial effects against numerous chronic conditions (Emara et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A high dietary intake of iron through meat or nutritional supplements is also a potential cause of iron overload 2. There have been animal and epidemiologic studies that suggest that a high iron status may increase the risk of heart disease 3–5. Since Sullivan's iron hypothesis proposal was put forth 3, the relationship between iron stores and atherosclerosis has become a topic that continues to be debated in the literature.…”
Section: Introductionmentioning
confidence: 99%